Effect of Continuous Positive Airway Pressure on Airway Inflammation and Oxidative Stress in Patients with Obstructive Sleep Apnea - Promsrisuk Tichanon; Khrisanapant Wilaiwan; Santamit Sopida; Pasurivong Orapin; Boonsawat Watchara; Intarapoka Banjamas (Canadian Respiratory Journal)
Background. Airway inflammation and oxidative stress may be linked in obstructive sleep apnea (OSA) patients. We determined the effectiveness of continuous positive airway pressure (CPAP) therapy in reducing fractional exhaled nitric oxide (FeNO) and malondialdehyde (MDA) levels in OSA patients. Methods. Thirteen patients with OSA and 13 normal controls were recruited. FeNO and MDA levels were measured in the controls and in OSA patients before and after three months of CPAP therapy. Results. FeNO and MDA levels were higher in the patients compared to the age and gender matched controls (FeNO: 25.9 ± 5.0 versus 17.5 ± 5.9 ppb, P<0.001; MDA: 14.6 ± 7.8 versus 2.1 ± 0.3 μmol/L, P<0.001). FeNO and MDA levels were lower post-CPAP compared to pre-CPAP (FeNO: 25.9 ± 5.0 versus 17.0 ± 2.3 ppb, P<0.001; MDA: 14.6 ± 7.8 versus 10.0 ± 6.4 μmol/L, P<0.01). Apnea-hypopnea index (15.9 ± 6.6 versus 4.1 ± 2.1/h, P<0.001) and mean arterial pressure (P<0.01) decreased following CPAP treatment. Daytime mean SpO2 (P<0.05) increased. Conclusion. Our study demonstrates that CPAP therapy yields clinical benefits by reducing upper airway inflammation and oxidative stress in OSA patients.